The effectiveness of cinnamon powder and cinnamon leaf extract to prevent Aeromonas hydrophila infection on striped catfish Pangasianodon hypophthalamus - Susanti, Erni; Wahjuningrum, Dinamella; Nuryati, Sri; Setiawati, Mia (Indonesian Society of Scientific Aquaculture (ISSA), 2021)
Striped catfish Pangasianodon hypophthalamus is one of the intensive cultured commodities. Disease outbreak becomes inevitable to prevent in a fish culture. One of the most frequent disease occurred in striped catfish is the motile aeromonas septicemia (MAS) disease caused by Aeromonas hydrophila. This study aimed to evaluate the effectiveness of 1% dietary cinnamon powder and 0.5% dietary cinnamon leaf extract on the immune response of striped catfish challenged with A. hydrophila. Striped catfish used in this study sizing of 5.80 ± 0.21 g. This study contained two phases, namely in vitro and in vivo tests. In vitro test contained inhibition zone and antibacterial tests, which demonstrates that 1% cinnamon powder and 0.5% cinnamon leaf extract are effective to inhibit A. hydrophila activity. In vivo test contained four treatments, i.e fish fed with 1% cinnamon leaf powder supplemented diet; 0.5% cinnamon leaf extract supplemented diet, positive control diet, and negative control diet. Each treatment was performed in three replications. The result showed that 1% cinnamon leaf powder supplemented diet obtained the best results to enhance the immune response of striped catfish higher survival rate value at 83.33% than the positive control diet (P<0.05). Keywords: Aeromonas hydrophila, Cinnamomum burmannii, extract, Pangasianodon hypophthalmus, powder. ABSTRAK Ikan patin Pangasianodon hypophthalamus termasuk komoditas yang banyak dibudidayakan secara intensif. Kendala budidaya seperti penyakit pun sulit untuk dihindari. Salah satu jenis penyakit yang kerap menyerang ikan patin yaitu penyakit MAS (motile aermomonad septicaemia) yang disebabkan oleh Aeromonas hydrophila. Penelitian ini bertujuan untuk menguji efektivitas 1% (w/w) tepung dan 0,5% (w/w) ekstrak daun kayu manis dalam pakan sebagai upaya pencegahan infeksi bakteri A. hydrophila pada ikan patin. Ikan patin yang digunakan berukuran 5,80 ± 0,21 g. Penelitian ini terdiri dua tahap yaitu uji in vitro dan uji in vivo. Hasil uji in vitro terhadap aktivitas antibakteri menunjukkan bahwa dosis 1% (w/w) tepung daun kayu manis dan 0.5% (w/w) ekstrak daun kayu manis efektif dalam menghambat pertumbuhan A. hydrophila. Uji in vivo terdiri atas empat perlakuan yaitu pemberian pakan dengan penambahan tepung daun kayu manis 1% (w/w), pemberian pakan dengan penambahan ekstrak daun kayu manis 0,5% (w/w), kontrol positif, dan kontrol negatif dengan masing-masing perlakuan terdiri atas tiga ulangan. Hasil penelitian menunjukkan bahwa penambahan 1% (w/w) tepung daun kayu manis dalam pakan memberikan hasil terbaik dalam meningkatkan respons imun ikan patin dengan tingkat kelangsungan hidup sebesar 83,33% lebih tinggi dibandingkan kontrol positif (P<0,05). Kata kunci: Aeromonas hydrophila, Cinnamomum burmannii, ekstrak, Pangasianodon hypophthalmus, tepung